MODEL PENELITIAN BUKU IBN AL-'ARABI WAHDAT AL-WUJUD DALAM PERDEBATAN - Abd Ghofir (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
One form of discipline and moral responsibility of a scholar, when writing a dissertation is the fulfillment of the demands of a new discovery according to the field of the scratch. Likewise, of course, a dissertation written by Dr. Kautsar Azhari Noer entitled "Wahdat al-Wujud Ibn al-'Arabi and Pantheism" adopted for a book title: "Ibn al-'Arabi Wahdat al-Wujud in the Debate", is expected to discover something new, especially in the field of Tasawwuf .But after reviewing the book, this paper has not or did not find new things or new findings. What is meant by the new findings by the authors, it is only a review of the findings previously written by WT. Stace in his book: Mysticism and Philosophy published by: JB. Lippincott Company, New York, 1990.This study does not at all mean to undermine Dr. Kautsar Azhari Noer's work, but merely examines the possibility of new insights about the book. Because the meaning of these new findings could cause controversy, as expressed by Prof. Dr. H. Muhaimin MA. Professor of UIN Malang, he called the book has found new findings.